Investigating Relationships between Youth Offending and Alternative Provision: Identified Protective and Risk Factors for Offending/Re-offending Based on ‘Type’ of AP and Duration in AP in England - Belkin, Liliana (International Journal of Population Data Science, 2025)
Objectives To investigate whether exposure to AP is associated with offending compared to a matched sample of young people using quasi-experimental techniques and time-to-event analyses To explore the factors associated with reoffending among young people exposed to AP and whether intensity (exposure length) and AP ‘type’ are associated with reoffending Method Utilizing the MoJ-DfE linked dataset for birth years 1993-2000, this study employs a quasi-experimental design to investigate the effect of AP (as an intervention) on the likelihood of offending/re-offending compared to young people in mainstream education. The analyses will compare differences between AP ‘type’ (e.g., PRU, vocational, etc.) and duration in AP (as measured by entry/exit data and dual enrolment). We will adopt a causal effect approach, using inverse proportional weighting to rebalance covariates distribution, coupled with Regression Adjustment to estimate the potential mean for offending for pupils in AP and mainstream and time-to-event/survival analysis to determine predictors of offending/re-offending. Results This paper will present preliminary results that contribute to our understanding of the influence of AP ‘exposure’ on youth offending patterns. This will include potential differences between AP ‘type’ and duration in AP across the intervention group and as compared to those in mainstream only. Analyses will include investigating differences for youth with SEND, CiN, and prior school exclusions to determine how these forms of educational ‘disruption’ may interact and vary by educational setting (AP, mainstream). Time-to-event analyses will contribute to understandings of offending/re-offending occurrences and AP and mainstream entry/exit points. This project includes a spatial disparity analysis component, investigating spatial/geographic differences in youth offending rates, available school options and differences in types of school settings predominantly serving youth offenders across England. Conclusion The results have relevance for policymakers and practitioners across the education, youth justice and care sectors and have the potential to inform policy/practice decisions that leverage protective characteristics of AP in mainstream schools to improve education and offending outcomes for youth offenders.